2015
DOI: 10.1038/srep14416
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial gene expression profile of pregnant sows with extreme phenotypes for reproductive efficiency

Abstract: Prolificacy can directly impact porcine profitability, but large genetic variation and low heritability have been found regarding litter size among porcine breeds. To identify key differences in gene expression associated to swine reproductive efficiency, we performed a transcriptome analysis of sows’ endometrium from an Iberian x Meishan F2 population at day 30–32 of gestation, classified according to their estimated breeding value (EBV) as high (H, EBV > 0) and low (L, EBV < 0) prolificacy phenotypes. For ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…Krueppel‐like factor 5 is a protein encoded by the KLF5 gene mapped to sheep chromosome 10. Some previous studies have indicated that KLF5 has potential important pleiotropic effect on regulating several cellular processes (development, differentiation, proliferation and apoptosis) and also has a significant role in regulation of embryo pre‐implantation litter size and prolificacy levels in pigs (Córdoba et al, ; Dang, Pevsner, & Yang, ). Another reproduction‐related gene, PDGFRL , was found to be under selection (top 1% F ST ) on sheep chromosome 26.…”
Section: Discussionmentioning
confidence: 99%
“…Krueppel‐like factor 5 is a protein encoded by the KLF5 gene mapped to sheep chromosome 10. Some previous studies have indicated that KLF5 has potential important pleiotropic effect on regulating several cellular processes (development, differentiation, proliferation and apoptosis) and also has a significant role in regulation of embryo pre‐implantation litter size and prolificacy levels in pigs (Córdoba et al, ; Dang, Pevsner, & Yang, ). Another reproduction‐related gene, PDGFRL , was found to be under selection (top 1% F ST ) on sheep chromosome 26.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important factors restricting female fertility, increasing litter size has received much more consideration (Naicy et al, 2016 ; Yang et al, 2017 ). However, litter size is a trait with low heritability in many livestock animals, including pigs (Córdoba et al, 2015 ) and goats (Shaat and Mäki-Tanila, 2009 ); therefore, traditional direct selection is ineffective. At present, marker-assisted selection (MAS), based on relevant genetic variants, is used extensively to improve traits with low heritability, such as those associated with growth and reproduction (Sharma et al, 2013 ; An et al, 2015 ; Tomas et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated analysis of miRNA–mRNA networks in placental tissues of Large White and Qingping sows revealed mRNAs and miRNAs associated with onset of labor, as well as a subset of genes that may play a role in regulation of gestation length [ 18 ]. Endometrial mRNAs and miRNAs in pregnant sows were also associated with extreme prolificacy phenotypes [ 17 ]. Present results now implicate miRNA–mRNA interactions in neonatal porcine uterine development.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, miRNAs were identified in adult endometrium [ 12 14 ] and in placental tissues [ 12 , 15 , 16 ] during early pregnancy. Endometrial [ 17 ] and placental [ 18 ] miRNA–mRNA interactions during pregnancy were also characterized. Little is known about miRNA expression in the developing uterus, or the roles of miRNAs in regulation of uterine gene expression during the perinatal period.…”
Section: Introductionmentioning
confidence: 99%